Analisis Pengaruh Penempatan Shearwall Pada Gedung Hotel Shafira - Harlika Mohammad Syahril; Wahyu Kartini; Sumaidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Hotel Shafira is a flat-shaped building with 10 floors, 12 meters wide and 72 meters long. These structures are prone to significant horizontal irregularities, reducing the overall efficiency of the building. The irregularity is partly due to the uneven distribution of the mass, as seen from the difference in the span of the portal between the back and front of the building which produces large cavities. Analysis with the ETABS program revealed that the eccentricity between the center of self and the center of mass reached 5 meters in the direction of the strong axis. This study overcomes the uneven load distribution by repositioning the shearwall through a trial and error approach, reducing eccentricity from 4 meters to 1.3 meters. This change not only increases the building's capacity, but also reduces the need for reclamation by 13.9% and shows the results of the pushover analysis in the Immediate Occupancy category. The placement of shearwalls has a significant influence on the capacity and stability of the building structure.